Implementasi Keperawatan Pemberian Aromaterapi Lavender Pada Pasien Hipertensi Dengan Masalah Nyeri Kepala - Prahardian Putri; Ismar Agustin; Jawiah Jawiah; Rahma Fitriya (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2026)
Background: Hypertension, also known as high blood pressure, is one of the leading causes of sudden death worldwide, and its prevalence continues to increase every year. About 1.28 billion people worldwide suffer from hypertension. South Sumatra in 2022, it was recorded that the number of hypertension patients in the province reached 6,234,389 people. Symptoms that are often felt by people with hypertension are headaches, especially in the neck and neck. This pain occurs due to damage to blood vessels caused by hypertension. Kepla Pain Can Be Overcome With Lavender Aromatherapy. Objective: To describe the implementation of nursing care in providing lavender aromatherapy to hypertensive patients with headache problems. Method: The design of this case study is descriptive in the form of a case study with a nursing care approach. The subject of the case study was 2 patients with hypertension. Patient 1 was 66 years old and patient 2 was 46 years old who had the same nursing problem Headache. This case study was conducted in the inpatient room of Ahmad Dahlan Hospital Muhammadiyah Palembang. Data collection techniques by way of observation, hearing and filling of case study instruments for 3 days in the treatment room. Results: After 3 days of implementation in both subjects with pain management: Lavender aromatherapy was found that there was an effective effect to reduce the pain scale from moderate to mild scale. Conclusion: With these results, it is expected and can apply and develop the implementation of Lavender Aromatherapy Pain Management nursing with headache problems in Hypertensive Patients.